Integrating the Prophet’s Teaching Methods with Deep Learning as a Solution to Superficial Learning - Novianti Hardini; Alfauzan Amin; Saepuddin Saepuddin (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Islamic education during the time of the Prophet Muhammad emphasized an integrative and transformative approach, combining cognitive, affective, and moral dimensions. However, modern education tends to promote superficial learning that focuses primarily on memorization and cognitive achievement, thereby failing to foster deep understanding and behavioral transformation among learners. This study aims to analyze the integration of the Prophet’s teaching methods with the deep learning paradigm as a solution to this issue. The research employs a library research method with a descriptive-analytical approach and content analysis technique, using sources such as the Qur’an, Hadith, classical Islamic literature, and contemporary academic journals. The findings reveal that the Prophet’s methods—exemplary conduct, interactive dialogue, and contextual learning—align with the three main pillars of deep learning: meaningful learning, mindful learning, and joyful learning. Critically, this model not only emphasizes conceptual understanding but also encourages moral reflection, value internalization, and behavioral transformation. The study implies that this integration can serve as a philosophical and pedagogical foundation for developing a more meaningful, humanistic, and transformative Islamic education in the modern era.